2003
DOI: 10.1021/cm0340227
|View full text |Cite
|
Sign up to set email alerts
|

Green Nanocomposites from Renewable Resources:  Plant Oil−Clay Hybrid Materials

Abstract: Green nanocomposites based on renewable plant oils have been developed. Curing of epoxidized plant oils in the presence of organophilic montmorillonite produced triglyceride−clay nanocomposites showing flexible property. A nanocomposite with homogeneous structure was obtained, in which silicate layers of the clay were intercalated and randomly distributed in the polymer matrix.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
110
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 196 publications
(110 citation statements)
references
References 24 publications
0
110
0
Order By: Relevance
“…Its advantages of high surface area, large aspect ratio (50 -1000), and platelet thickness of 10 Å make it suitable for reinforcement purposes. 10 The inorganic surface of MMT has also been modified by organic replacement of the interlayer sodium ions by various organic cations to make the platelets more compatible with polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Its advantages of high surface area, large aspect ratio (50 -1000), and platelet thickness of 10 Å make it suitable for reinforcement purposes. 10 The inorganic surface of MMT has also been modified by organic replacement of the interlayer sodium ions by various organic cations to make the platelets more compatible with polymers.…”
Section: Introductionmentioning
confidence: 99%
“…2 Bio based nanocomposites are a more recent addition to the field. [3][4][5] In this contribution, it will be shown that wood fibers can be plated using nanoclays. In this way, the natural hydrogen-bonding affinity between fibers can be significantly reduced, enabling nanoplated fibers to be used in various applications such as improving fluff pulp quality.…”
Section: Introductionmentioning
confidence: 99%
“…[30] An acid-catalyzed curing of epoxidized plant oils in the presence of an organophilic montmorillonite produced organic-inorganic hybrids with a homogeneous structure at the nanometer level. Furthermore, high-performance hybrid coatings based on renewable plant oils have been developed.…”
Section: Introductionmentioning
confidence: 99%